Ecommerce drivers and marketing partnerships in successful export marketing of Finnish born globals - Penttinen, Jukka (2015)
This study examines the utilization of ecommerce and marketing partnerships as part of born global internationalization strategies. The study will combine the existing literature of born global internationalization, export marketing strategies and ecommerce as part of internationalization to form an understanding on how two Finnish health and welfare sector born globals internationalize, and how ecommerce drivers affect their internationalization. Because of the explorative nature of the study, the research was conducted as a case study.